Chlorpropamide-alcohol flushing: a dominantly inherited trait associated with diabetes. Issue 6151 (2nd December 1978) - Leslie, R D; Pyke, D A
Abstract : A simple test was devised to identify people susceptible to chlorpropamide-alcohol flushing (CPAF). Subjects were given a placebo tablet, followed by sherry 12 and 36 hours later. They then received a chlorpropamide tablet and sherry again after 12 and 36 hours. This single-dose challenge test was given to non-insulin-dependent diabetics, insulin-dependent diabetics, and normal subjects. CPAF was common in the non-insulin-dependent diabetics but rare in the other groups. When the test was used in identical twins and families of affected subjects CPAF appeared to be a dominantly inherited trait. We conclude that facial flushing after alcohol in people taking chlorpropamide is related to non-insulin-dependent diabetes, especially when there is a strong family history of diabetes, but not to insulin-dependent diabetes. It is a dominantly inherited trait.